HUBUNGAN GANGGUAN EMOSIONAL DAN PERILAKU DENGAN KEPUASAN HIDUP REMAJA DI SEGOROYOSO, PLERET, BANTUL, YOGYAKARTA - Fitri Dian Kurniati; RR Viantika Kusumasari (Universitas Respati Yogyakarta, 2021)
The Relationship Between Emotional and Behavioral Disorders and Adolescent Life Satisfaction in Segoroyoso, Pleret, Bantul, YogyakartaBackground : Emotional and behavioral disorders become a serious problem in adolescent development. This can reduce productivity and adolescent life satisfaction. Life satisfaction influences adolescent life. The life satisfaction of adolescents serves to overcome negative environmental impacts. The low life satisfaction of adolescents has resulted in various problems. If adolescents have high life satisfaction, adolescents can prevent and reduce risk behaviors that arise so as to facilitate adolescent development to be more optimal. Objective : To analize the relation between emotional and behavioral disorders with adolescent life satisfaction adolescent of Segoroyoso, Pleret, Bantul, Yogyakarta. Methods : This research method is a non-experimental research with a cross-sectional approach. The number of samples in the study were 36 respondents, sampling with total sampling technique. Statistics analysis using Spearman's test. Results : The results of this study showed that emotional and behavioral disorders of adolescents are almost in the normal category (47.2%) and 91.7% of adolescent life satisfaction in the high category. The p value obtained is 0.106. Conclusion : There is no significant correlation between emotional and behavioral disorders with adolescent life satisfaction.